DAMPAK PENGGUNAAN GADGET BAGI ANAK USIA DINI DI DESA EHO HILISIMAETANO - Asnat Herlindawati Buulolo (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
This research is motivated by the use of gadgets regardless of age, especially in early childhood. The impact of gadgets on young children is very large. This research aims to determine the impact of gadgets on young children. This type of research is qualitative research with a case study method. The data source in this research is the community (parents) of early childhood in Eho Hilisimaetano Village. There is data analysis used in the research, namely reduction, data modeling and drawing conclusions. The findings of this research show that there is a negative impact of gadgets on young children, namely: (1) young children are familiar with gadgets; (2) young children are very familiar with gadgets; (3) young children have a large focus on gadgets; (4) young children are fussy when not using gadgets; (5) young children consider gadgets as fun games (6) young children become individuals who are good at imitating; (7) gadgets cause children's habits to change; (8) young children dare to lie or steal time to play with gadgets; (9) young children experience eye health problems; (10) parents deliberately give gadgets to young children. So it can be concluded that gadgets have a negative impact on the growth and development of early childhood. So researchers suggest that parents use the findings of this research as a reference in overcoming the impact of gadgets on early childhood. It is hoped that the Village Head will use this research as an experience so as to encourage the community to be able to overcome and control the use of gadgets in early childhood. And can be used as motivation, a source of reference and knowledge for future researchers, BK students and for UNIRAYA